Production and intra-regional trade in packaging materials, printed paper and paper production (Woodbridge, Reed and Associates Vancouver, BCCA, 1986)
Reviews the CARICOM converted paper products industry highlighting constraints facing it. Outlines ways of improving the industry on a short and long term basis. Summarizes existing market conditions focusing on individual products. Gives overview of the industry in individual countries focusing on production, consumption, imports, and exports. Proposes strategy for the development of intra-regional trade within CARICOM which emphasizes inter alia, import substitution, development of new products, advertising, timely delivery, and quality control.
IDS